Impact of ATS Flight Plan Rejection on Air Traffic Services at AirNav Indonesia Palembang - Syalaby Nadiem Javani; Susi Suhardianti; Lina Rosmayanti (International Journal Of Humanities Education and Social Sciences (IJHESS), 2026)
The increase in air traffic volume at AirNav Indonesia Palembang Branch, along with the expansion of service sectors, has led to a significant rise in the number of flight plans processed by the ATS System. This condition increases the potential occurrence of flight plan rejected events, which may affect the quality of air traffic services. This study aims to analyze the impact of flight plan rejected by the ATS System on air traffic services at AirNav Indonesia Palembang Branch. A quantitative research method was employed, with data collected through questionnaires, observations, and documentation studies. The research population consisted of 56 Air Traffic Controllers (ATC), all of whom were included as research samples. Data analysis was conducted using validity tests, reliability tests, descriptive statistics, normality tests, correlation analysis, and simple linear regression.